MANAGEMENT MODEL OF TEACHER TRAINING PROGRAM ON ENHANCING WORK PERFORMANCE: EXPLORATORY SEQUENTIAL DESIGN AT SMPN 3 NUMFOR BARAT - Erwanto Guntoro; Sri Langgeng Ratnasari; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The importance of teacher performance in improving achievement to determine the quality of education and school performance, This study is an Exploratory Sequential mixed method design study. aims to influence leadership, work motivation, and organizational culture on teacher performance and achievement, both partially and simultaneously with Exploratory Sequential Design . This approach combines qualitative and quantitative methods, starting with an in-depth exploration of the factors that influence the effectiveness of teacher work performance, followed by testing the quantitative model. This research was conducted at SMP Negeri 3 Numfor Barat in a remote area. To achieve the objectives of this study, the researcher applied Exploratory Sequential mixed method design research with a case study approach . In the qualitative stage, the research data was collected through observation, in-depth interviews with 1 head of educational unit and 10 subject teachers, and document analysis to identify needs, challenges, and best practices in management. The research data was processed through the stages of data collection, data presentation, data reduction, and data conclusion drawing. To ensure the validity of the research data, the researcher conducted data confirmation and credibility by involving the Education Office for the development of educational resources and school supervisors. The results of the study indicate that: (1) the teacher training management model in improving work performance that has been implemented in remote areas consists of the planning, organizing, implementing and evaluating stages. (2) The function of the teacher training management model in improving work performance that has been implemented in remote areas runs effectively and efficiently. The results of this study provide important information for the government, school supervisors, principals and teachers. leadership, work motivation, and organizational culture simultaneously have a positive and significant effect on teacher work performance.